2022
DOI: 10.1590/1516-3180.2021.1047.r.19052022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasonography learning between distance teaching and traditional methodology. An educational systematic review

Abstract: INTRODUCTIONLearning is an event consisting of a goal, a training activity and an appraisal. 1 The aim is to have a total instructional experience, associated with the usual descriptors. 1 The method for acquiring further information is not merely a matter of obtaining data (surface learning); additionally, it involves the capacity to interpret it and feasibly do this. 2 One essential feature of the learning method relates to student motivation. 3 Student motivation involves mutual communications within ambien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Dies lässt sich so interpretieren, dass obwohl die Kurse erstmalig virtuell stattfanden, möglicherweise bei einer relevanten Zahl der Teilnehmer bereits eine positive Voreingenommenheit gegenüber virtuellen Fortbildungskursen im Generellen vorhanden war, da diese in anderen Fachbereichen und bei anderen Themenschwerpunkten nach über einem Jahr pandemiebedingter Einschränkungen bereits gang und gäbe waren. Bisherige wissenschaftliche Erhebungen zu rein webbasierten Unterrichtsformaten in der Sonographie lagen bereits insbesondere für den Bereich der universitären Lehre im Rahmen der medizinischen Curricula vor [ 19 ], weniger Untersuchungen bestehen bisher für rein ärztliche Fortbildungen. Häufig wird bei der Übertragbarkeit der Ergebnisse lehrwissenschaftlicher Studien dabei eine demografisch assoziierte Korrelation in der Akzeptanz virtueller Lehrformate postuliert [ 5 ].…”
Section: Diskussionunclassified
“…Dies lässt sich so interpretieren, dass obwohl die Kurse erstmalig virtuell stattfanden, möglicherweise bei einer relevanten Zahl der Teilnehmer bereits eine positive Voreingenommenheit gegenüber virtuellen Fortbildungskursen im Generellen vorhanden war, da diese in anderen Fachbereichen und bei anderen Themenschwerpunkten nach über einem Jahr pandemiebedingter Einschränkungen bereits gang und gäbe waren. Bisherige wissenschaftliche Erhebungen zu rein webbasierten Unterrichtsformaten in der Sonographie lagen bereits insbesondere für den Bereich der universitären Lehre im Rahmen der medizinischen Curricula vor [ 19 ], weniger Untersuchungen bestehen bisher für rein ärztliche Fortbildungen. Häufig wird bei der Übertragbarkeit der Ergebnisse lehrwissenschaftlicher Studien dabei eine demografisch assoziierte Korrelation in der Akzeptanz virtueller Lehrformate postuliert [ 5 ].…”
Section: Diskussionunclassified
“…It also has the advantage of a better connection between the student and the tutor and improvement of the tutor's ultrasound skills through teaching [30,31,32]. Several studies demonstrated similar performance of students taught via the peer-to-peer approach versus classic faculty teaching [9,33,34,35]. The classic approach of didactic presentations has the advantage that it can target large audiences, is an established methodology, does not need further funding from the university, and is appropriate, for instance, for teaching the fundamentals of ultrasound.…”
Section: Efsumb and Wfumb Position Papers Regarding Students' Ultraso...mentioning
confidence: 99%
“…Incorporation of ultrasound education into medical schools has become a widespread trend worldwide [3,4]. This is reflected in a fast-growing body of literature [5] which is summarized by five meta-analyses and further scoping reviews [6,7,8,9,10,11,12]. Both the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) [4] and the World Federation of Ultrasound in Medicine and Biology (WFUMB) issued position papers suggesting "that ultrasound should be used systematically as an easily accessible and instructive educational tool in the curriculum of modern medical schools" [3,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation